ANALYSIS OF NUTRITIONAL CONTENT OF TORBANGUN (Coleus amboinicus Lour) LEAF BISCUIT - Donal Nababan (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: One of the local food ingredients that can be utilized as a complementary food is a torbangun leaf. Torbangun leaf is usually consumed in the form of torbangun leaf soup or served as vegetables with main meal. Torbangun is rich in iron, vitamin C, energy, protein, fat that is very beneficial for infant growth and is widely available in the market with cheap price. Torbangunleaves, especially when made into powder, can be processed into a wide range of food products such as biscuit, but needs several intervention trials to search its long shelf life with high energy density. Methods: The purpose of this research is to study the formulation of torbangun leaf biscuit and to analyze the nutrient content in meeting the nutritional requirements of child stunting aged 12-18 months. Organoleptic test was conducted with 5 point hedonic rating test. This study used Anova test to see the mean difference in the assessment of leaf biscuits torbangun. Results: With the addition of 10% (A), 20% (B), and 30% (C) torbangun leaf powder in every 100 gr biscuit, the organoleptic test showed that biscuit with 20% of torbangun flour had the highest organoleptic score on taste, flavor, texture and color. The biscuit contents energy and protein similar to the commercial fortified (PMT) biscuit with high content of iron and calcium. Comparedwith the PMT biscuits, the torbangun leaf biscuit meets the energy criteria (at least 400 kcal/100gr) but slightly having lower protein (less than 8gr/100gr). However iron content of torbangun biscuit equals the upper range of the PMT biscuit (4-7.5 mf/100gr) and very high calcium content (almost 10 times higher than the PMT biscuit). Consclusions: The selected biscuits with 20% torbangun leaf powder will be used in the following intervention study promoting complementary food recommendation with fortified biscuits.